Insight into the role of Ti addition on the evolution of γ/γʹ microstructure in Co–Al–W–Ti quaternary alloy using multicomponent phase-field model - Min Guo; Xingbing Zhang; Jia Chen; Borong Cui; Tingting Cui; Min Yang; Jun Zhang (Journal of Materials Research and Technology)
Ti is a promising γʹ-stabilized element in innovative γʹ-hardened Co-based superalloys that improves their microstructural stability and high-temperature mechanical properties. However, the effect of Ti addition on the kinetics of γʹ precipitation is still an open question. In this study, the γ/γʹ microstructural evolutions in Co–Al–W–Ti quaternary superalloy during aging were simulated using the multicomponent phase-field model. The impact of Ti element on the evolution processing and mechanism of γʹ precipitate was analyzed. During the simulation, the calculation of phase diagrams (CALPHAD) method was combined to provide quantitative thermodynamic driving force for the precipitation of γʹ phase. The results indicate that Ti element addition increases the volume fraction and the cube degree of γʹ phase, and the influence of Ti content on the γ′ volume fraction is a result of the combined action of Ti distribution itself and Ti-induced W redistribution. The temporal evolution of γʹ equivalent radius shows that the coarsening of γʹ precipitates containing Ti follows the classical LSW theory. As the Ti content increases, the coarsening rate of γʹ accelerates due to a larger diffusion driving force and higher chemical mobility. This study presents a new approach for designing multicomponent Co-based superalloys with excellent microstructural stability, and also reveals the effect of Ti addition on the evolution of γʹ in innovative Co-based superalloys.